KUALITAS PELAYANAN PADA BIDANG DATA DAN FORMASI KANTOR BADAN KEPEGAWAIAN DAERAH KABUPATEN SIGI - Yulianita, Eka (Katalogis, 2016)
This study aimed to analyze the quality of service in the field of Data and Formation Office of the Regional Employment Board Sigi using qualitative descriptive analysis. The number of informants in this study were as many as five (5) informant. The results showed that of the five indicators of service personnel are on the dimensions of both categories. The results showed that overall the service users at the Office of the Regional Employment Board Sigi states get good service from the concierge / apparatus Office Regional Employment Agency Sigi. In an effort to enhance service quality field services personnel need to make improvements in terms of both infrastructure and personnel resources. In addition to the need to set minimum service standards in the delivery of services to be more effective as well as the need to provide training to officers / personnel as often as possible.